The Role of Hypomethylating Agents Prior to Allogeneic Hematopoietic Stem Cells Transplantation in Acute Myeloid Leukemia and Myelodysplastic Syndrome - VN Ovechkina; SN Bondarenko; EV Morozova; IS Moiseev; AA Osipova; TL Gindina; AI Shakirova; TA Bykova; AD Kulagin; IA Samorodova; EV Karyakina; EA Ukrainchenko; et al. (Клиническая онкогематология)
Background & Aims. The aim of the study was to evaluate the efficacy and safety of azacytidine and decitabine prior to allogeneic hematopoietic stem cell transplantation (allo-HSCT) in acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), chronic myelomonocytic leukemia and juvenile myelomonocytic leukemia.